Determination of Total Phenolic Content of Ethanol Extract of Black Turmeric Rhizome (Curcuma caesia Roxb.) by Folin-Ciocalteu Method Spectrophotometrically - Zulfisa, Zulfisa; Ulfa, Faizah; Marjoni, Mhd Riza (International Journal of Engineering, Science and Information Technology, 2024)
Due to the high concentration of secondary metabolites present in nearly every part of the plant, black turmeric (Curcuma caesia Roxb.), a traditional medicinal plant, may provide a natural supply of antioxidants. The objective of this research is to determine the total phenolic content of the black turmeric rhizome ethanol extract using UV-Vis spectrophotometry. The extraction was performed by macerating the material in a solution consisting of 70% ethanol. We employed the Folin-Ciocalteu method to ascertain the total phenolic content, which was then represented as gallic acid equivalent (GAE). The research revealed that there were 192 mg GAE/g of total phenolic content in the ethanol extract of black turmeric rhizome. According to the metrics measuring total phenolic content, the black turmeric rhizome ethanol extract may have antioxidant properties. This study provides important information about black turmeric's antioxidant potential which can be used to develop herbal products based on this plant.